Prognostic significance of Ki-67 index value at the primary breast tumor in recurrent breast cancer - NISHIMURA, REIKI (D.A. Spandidos, 2014)
The Ki-67 index value is a prognostic factor in primary breast cancer and is a proliferation marker that also distinguishes between luminal type A and type B breast cancer. Moreover, a change in Ki-67 index values due to treatment and recurrence is considered to be important in treating breast cancer. In this study, we investigated whether the baseline Ki-67 value in the primary tumor is useful as a prognostic factor following disease recurrence. Immunohistochemical analysis of the Ki-67 index was performed on 4,701 patients with primary breast cancer from 1987 until March, 2013. Among these patients, there were 666 consecutive cases exhibiting recurrence after primary surgery. The fraction of proliferating cells was based on a count of at least 500 tumor cells in the area including the hot spot. The Ki-67 values were divided into 3 groups, namely <20, ≥20 and ≥50%. The investigated items included estrogen receptor (ER), progesterone receptor (PgR), human epidermal growth factor receptor 2 (HER2), tumor size, nodal status for the primary tumor, recurrence site (soft tissue, bone and viscera) and disease-free interval (DFI). The Cox’s proportional hazard model was used to perform univariate and multivariate analyses of the factors associated with overall survival (OS) following recurrence. The median follow-up period was 65.9 months in the surviving group. The median Ki-67 value at baseline was 20% in all the cases and 27% in the recurrent cases. The Ki-67 values were low (24%) in patients with bone metastasis and significantly higher in patients with liver or brain metastasis (38 and 55%, respectively). Moreover, DFI was found to be inversely correlated with the Ki-67 values. Univariate analysis was performed to identify the prognostic factors for OS after recurrence. The significant factors included tumor size, lymph node status, ER, PgR, DFI, recurrence site and Ki-67 index value. Among these factors, a multivariate analysis identified the Ki-67 index value in the primary tumor as an independent significant factor, particularly in luminal type tumors. The Ki-67 index value in the primary tumor was a significant prognostic factor for OS after disease recurrence. It is, therefore, important to take the Ki-67 index value into consideration for the treatment and follow-up of breast cancer patients.